Analysis of field-free region formed by parametric positioning of a magnet pair for targeted magnetic hyperthermia: DOI: 10.48129/kjs.16097 - Küçükdermenci, Serhat (Kuwait Journal of Science, 2022)
One of the challenges in using magnetic fluid hyperthermia in practical applications is the limited control of magnetic nanoparticle oscillations. In this study, we investigated how the form and location of a static magnetic field-free region can be modified by the symmetrical and asymmetrical positioning of a magnet pair. The gradient patterns in the workspace were estimated using a finite element method simulation. On an experiment platform, measurements were taken using a point probe. It has been demonstrated that parametric changes in distance and angle allow changing of the form and location of the field-free region. Field-free regions can shrink and have shapes similar to a line or point. The focus of the field-free region can be directed to various parts of the target object. The mapping of gradient patterns formed by a magnet pair for the use of targeted magnetic fluid hyperthermia is described for the first time in this paper. Furthermore, the findings highlight the significance of the fit between the target objects and the created gradient models.